Voters’ Attitudes towards the Gender Quota System in Elections in Poland and the Possibility of Its Modification - Tomczak, Łukasz; Iwański, Rafał; Zawadzka, Katarzyna (Historia i Polityka, 2023)
The article concerns the support for the gender quota system in the elections in Poland. The research was conducted on a double sample of adults for a representative national research, by means of quota sampling method (n = 2119). The respondents who believed that there is insufficient representation of women in parliament outnumbered those with the opposite opinion. We have observed a reluctance among the respondents to introduce solutions aimed at strengthening women’s representation. The difference in views were determined by political preferences, gender, age, domicile, and education. Women and leftist supporters more frequently believed that there are too few women in parliament and supported quotas, as opposed to men and persons with right-wing views. The differences were observed in the youngest age category, where women more often opted for quotas than men.